2014
DOI: 10.1638/2014-0056.1
|View full text |Cite
|
Sign up to set email alerts
|

ALFAXALONE AS AN INTRAMUSCULAR INJECTABLE ANESTHETIC IN KOI CARP (CYPRINUS CARPIO)

Abstract: Fish are commonly anesthetized with MS-222 (tricaine methanesulfonate), a sodium-channel-blocker used as an immersion anesthetic, but its mechanism of action as a general anesthetic is uncertain. Alfaxalone is a neurosteroid that acts at the GABA(A) receptors. Alfaxalone has been evaluated and was deemed successful as an immersion agent in koi carp. Alfaxalone is an effective intramuscular anesthetic in multiple species. A reliable intramuscular anesthetic in fish would be useful in multiple settings. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The carp used in this study were considered to be able to maintain their HR, even with a short-term decrease in water temperature due to heat tolerance, and no significant change was observed during the study period compared to normal water temperature. Moreover, alfaxalone administration did not lead to any significant changes in HR or significant differences between water temperature groups at any time point, corroborating the findings by Bailey et al [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The carp used in this study were considered to be able to maintain their HR, even with a short-term decrease in water temperature due to heat tolerance, and no significant change was observed during the study period compared to normal water temperature. Moreover, alfaxalone administration did not lead to any significant changes in HR or significant differences between water temperature groups at any time point, corroborating the findings by Bailey et al [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although there are few reports of alfaxalone intramuscular administration in carp, Bailey et al [ 7 ] reported lethal side effects such as respiratory arrest upon intramuscular administration of 10 mg/kg alfaxalone in carp. In this study, the risk of apnea was predicted, but respiratory depression due to alfaxalone administration was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anesthetics are necessary for reducing stress and strife in fish for a variety of activities ranging from transporting to surgical operations also it is important for sampling [1][2][3], egg extraction (artificial reproduction), drug or vaccine injection, physical examination, blood sampling, biopsy, or biometry for aquatic animals. The efficiency, safety and harm of anesthetics compound depend on fish species, fish size, physicochemical properties of water (water quality), environmental factors (temperature), type of anesthetic drug and drug delivery method [4][5][6].…”
Section: Introductionmentioning
confidence: 99%